The Schematic Thought of Cities beyond the Hermann Theory - Tuqa Raad Alrobaee; Ibrahim Jawad Al Yousif (Iraqi Journal of Architecture and Planning, 2018)
The research focuses on one of the important theories on the human brain, how to understand the nature of human thinking and predict its behavior, Hermann's theory, by introducing a new philosophical vision,looking for the center in Herman's model, Called the inner senses as adopted by the philosopher Ibn Sina.Thus, the research problem summarized as follows: the absence of a center in Hermann's model of organizing and coordination between the four parts of his brain that he proposed. The research adopted the hypothesis that there is a close relationship between the inner senses as proposed by Ibn Sinaand Hermann's model, To the supposed center of this model), and the research aims through this proposal to find new symbolic forms developed model Hermann show the presence of the center and reflect the state of dynamism and change that characterizes the brain.The study found that the sense of "force" of common sense represents the center in the Hermann model, while the imaginary (pictured) represents part A, the image represents the creative part D, the illusion represented the part C, and the memory (the clipboard) represents part B.The study examined four models of cities in which different ways of thinking used, in which a certain part of the brain was clearly dominated by the four parts. However, the research found that despite the dominance of a particular part, there is a role for other parts but in varying proportions. The four parts are (common sense) which called in our research (human integration) which is the supposed center of the brain.